2010
DOI: 10.3892/etm.2010.164
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of microRNAs, miR21 and miR23a in human liver cancer cells treated with Coptidis rhizoma aqueous extract

Abstract: Abstract. Coptidis rhizoma (cr; huanglian in chinese) has been used for the treatment of cancer in chinese medicine, and recent studies have supported its use in cancer therapy. micrornas (mirnas) play an important role in the pathophysiology of human cancers. We examined alterations in the miRNA profile of hepatocellular carcinoma (HCC) cells after treatment with Coptidis rhizoma aqueous extract (craE). an on-chip microarray method was used to detect alterations in the expression profile of miRNAs in human hc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Although the up-regulation of microRNAs in MHCC97-L cells after treatment with the Coptidis rhizoma aqueous extract [54] and decreased levels of miR-21-5p in multiple myeloma cells after berberine treatment have been reported [55], we present the first evidence that the expression levels of miR-21-3p (previously named miR-21*) increased after berberine treatment in the HepG2 human hepatoma cell line. Based on multiple species alignments of the 18 currently available mammalian genomes, we found that one nucleotide substitution, MIR21 (+54 G to C), replaced the fifth nucleotide of the conserved seed region of miR-21-3p.…”
Section: Discussionmentioning
confidence: 58%
“…Although the up-regulation of microRNAs in MHCC97-L cells after treatment with the Coptidis rhizoma aqueous extract [54] and decreased levels of miR-21-5p in multiple myeloma cells after berberine treatment have been reported [55], we present the first evidence that the expression levels of miR-21-3p (previously named miR-21*) increased after berberine treatment in the HepG2 human hepatoma cell line. Based on multiple species alignments of the 18 currently available mammalian genomes, we found that one nucleotide substitution, MIR21 (+54 G to C), replaced the fifth nucleotide of the conserved seed region of miR-21-3p.…”
Section: Discussionmentioning
confidence: 58%
“…Tomimaru et al (2010) have demonstrated that miR-21 has an effect in the modulation of the response to IFN-␣/5-FU favoring the clinical response and survival. This miRNA is the first to be studied as a therapeutic tool and other two studies (Connolly et al, 2008;Zhu et al, 2011) have shown that the transfection of tumor cells with antisense oligonucleotides specific for mir-21 leads to a reduction of the cell growth and survival. Likewise studies by Xu et al (2011a), Bihrer et al (2011), Marquez et al (2010 have shown that serum levels of miR-21 are increased with a progressive course from chronic hepatitis to cirrhosis and hepatocellular carcinoma.…”
Section: Mir-21mentioning
confidence: 99%
“…SLC6A14 is a target for estrogen receptor (42). c-Myc also influences SLC6A14 expression, not directly but indirectly via miR-23a; c-Myc suppresses the expression of miR-23a (11), and SLC6A14 is a documented target for miR-23a (43).…”
Section: Slc6a14 In Cancer and The Relevance Of Its Transport Functiomentioning
confidence: 99%